PENYELESAIAN SENGKETA DALAM PERJANJIAN PERDAGANGAN MEGAREGIONAL: REGIONAL COMPREHENSIVE ECONOMIC PARTNERSHIP (RCEP) AGREEMENT - Rizky Banyualam Permana (Arena Hukum, 2023)
In 2020, the Regional Comprehensive Economic Partnership (RCEP) agreement was signed. The RCEP Agreement is the largest regional trade agreement in the world in terms of total GDP. In the Asia-Pacific region, there are various regional and bilateral trade agreements that lead to not only overlapping of substantive provisions, but also overlapping of dispute settlement for a. It is important to review the procedural aspects RCEP agreement to as the means to enforce the rules and commitments in the RCEP for its member countries, especially with regard to Indonesia. This study concludes that although the RCEP has its own dispute resolution mechanism procedures, the formulation of the provisions in the RCEP shows compromise of the negotiation outcome, typical in ASEAN agreements. This would become the hindrance to the effective implementation and implementation of the agreement.